Scientific Academic Writing: The Difficulties of Writing Abstracts of Theses and Dissertations in Biological Disciplines - Mahdi Ra’uf, Mayyada (International Journal of Psychosocial Rehabilitation, 2020)
In all scientific disciplines, academic writing has been a critical domain of research in general. Then, the necessity to develop academic writing raises and the process may be more significant and complicated as the students shift to a higher level of education. Although many studies have been devoted to examining the textual and phrasal characteristics of the dissertation and theses as academic genres, few have been concerned with substantive problems of EFL postgraduates during writing these genres, particularly in English for Specific Academic Purposes ESAP and scientific disciplines. The dissertations and the theses embody one of the powerful forms of scientific discourse and scientific communication so; the abstract of theses and dissertations is a crucial genre that has a vital role in scientific academic writing particularly for foreign learners of English language. The weight of this compulsory genre is strengthened by the important function that it performs in the academic practice in theses /dissertations, even though this function the abstract genre is neglected in the literature of ESAP studies. Abstracts are almost global in scientific theses /dissertations where there are fundamental similarities concerning language, significance, and structure. The current study sheds light on the characteristics of the language of the abstract as a scientific academic genre and considers its importance in theses /dissertations. The models of the abstract, as well as the common structures, are also highlighted in the study. It tackles and examines the obstacles faced by Iraqi EFL postgraduates in biological disciplines during writing the abstracts of their theses /dissertations in English language. To reach this goal, the researcher uses semi-structured interviews that answer the principal two questions of the study, the first is what are the main difficulties faced by Iraqi EFL postgraduates of biology during writing this academic genre? And the second is what are the causes that create these difficulties? The participators were 32 MSc and PhD postgraduates in seven biological disciplines at six different universities. To collect the data of the study a questionnaire with two parts was used the first involved closed questions while the second involved open-ended questions. The results showed that the Iraqi EFL postgraduate students in all biological disciplines as novice writers face similar difficulties in writing the abstracts of their theses /dissertations in English language. Some of these difficulties are related to language use and linguistic realizations like grammar, vocabulary, and words. Others are related to the structural organization of the abstract. These difficulties are contributed to the lack of previous experience and knowledge about academic writing and abstract writing models, in addition, the lack of integration between language development and academic development.